92 Presence and Etiology of Erectile Dysfunction in Peyronie's Disease as Demonstrated by Color Doppler Duplex Ultrasound. Issue 1 (1st April 2022) - Haehn, D; Pathak, R; Parikh, K; Ball, C; Broderick, G
ABSTRACT: Introduction: Peyronie's Disease (PD) can coexist with erectile dysfunction (ED). International guidelines recommend that management of PD include an assessment of each patient's ability to initiate and sustain erection. PD causes significant stress to the patient and his partner; that distress may limit their ability to assess adequacy of penile rigidity. Further complicating evaluations based on history is the fact that PDE5-Inhibitor use is common. Objective: The primary aim of this study is to non-invasively assess vascular erectile integrity in the setting of PD. Methods: 1490 patients who underwent intracavernous injection (ICI) followed by Color Doppler Duplex Ultrasound (CDDU) at our institution were retrospectively analyzed. CDDU findings were recorded following injection of low dose alprostadil (10-20 mcg) and again after a period of privacy and visual sexual stimulation. CCDU findings including peak systolic velocities (PSV), and resistive indices (RIs) were recorded. Arterial insufficiency (AI) was defined as either a post-stimulation PSV < 25 cm/sec (severe AI) or a PSV 25-34.9, RI ≥ 0.9(mild AI). Cavernous Venous Occlusion Disease (CVOD) was defined as post-stimulation PSV ≥ 35 cm/sec with RI < 0.9. Mixed was defined as post-stimulation PSV 25-34.9 with RI < 0.9. Vascular normal was defined as post-stim PSV ≥ 35 with RI ≥ 0.9. Results: Our cohort of 1490 patients included 900 (60.4%) with a complaint of both PD + ED; 461 (30.9%) with complaint of ED only and 129 (8.7%) with complaint of PD only. Following ICI with PGE1, 310 men were found to have PD and 767 were found to have PD + ED. Patients with a CDDU confirmed diagnosis of PD alone were younger (median: 56.9 vs. 60.8 y, p < 0.001), less likely to have hypertension [103/310 (33.2%) vs. 365/767 (47.6%), p < 0.001], less likely to have used PDE-5 inhibitor [219/310 (70.6%) vs. 616/767 (80.3%), p < 0.001], and less likely to have failed to a PDE-5 inhibitor [142/219 (64.8%) vs. 484/616 (78.6%, p < 0.001]. Diabetes was slightly more common in men with PD + ED compared to PD [270 (35.2%) vs. 94 (30.3%), p = 0.063], but not statistically significant. CDDU diagnoses for men with ED + PD were: AI 262/767 (34.2%), CVOD 305/767 (39.8%), mixed vascular ED 200/767 (26.1%). By definition all men with PD alone were vascular normal. Self-assessments by SHIM scores were abnormal in both groups ED + PD and PD [median(interquartile range): 10 (5 – 17) vs. 14 (8 – 20), p< 0.001]. Conclusions: By history alone, patients with ED + PD vs. PD only can't reliably be identified. This is likely related to the distress caused by PD and the tendency to physicians to treat or patients to self-medicate all erectile complaints with PDE5-Inhibitors. For non-invasive treatments distinguishing between ED + PD vs. PD is not critical. Before any patient is triaged to surgical intervention an evidence-based assessment of vascular erectile integrity should be performed. In our cohort of men, Doppler analysis demonstrated that at least 6 out of 10 PD patients have some form of vascular ED. Disclosure: No